1996
DOI: 10.1128/jb.178.19.5627-5635.1996
|View full text |Cite
|
Sign up to set email alerts
|

The nucleotide sequence of the Pseudomonas aeruginosa pyrE-crc-rph region and the purification of the crc gene product

Abstract: The gene (crc) responsible for catabolite repression control in Pseudomonas aeruginosa has been cloned and sequenced. Flanking the crc gene are genes encoding orotate phosphoribosyl transferase (pyrE) and RNase PH (rph). New crc mutants were constructed by disruption of the wild-type crc gene. The crc gene encodes an open reading frame of 259 amino acids with homology to the apurinic/apyrimidinic endonuclease family of DNA repair enzymes. However, crc mutants do not have a DNA repair phenotype, nor can the crc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 41 publications
5
79
0
Order By: Relevance
“…2), which was in agreement with previous studies on catabolite repression in this strain (19). Mucoid PDO300 (a mucA22 derivative of PAO1) contained approximately 1.5-fold more zwf-lacZ activity than the parent when grown on glycerol but still showed strong catabolite repression of zwf-lacZ with succinate (Fig.…”
Section: Resultssupporting
confidence: 91%
“…2), which was in agreement with previous studies on catabolite repression in this strain (19). Mucoid PDO300 (a mucA22 derivative of PAO1) contained approximately 1.5-fold more zwf-lacZ activity than the parent when grown on glycerol but still showed strong catabolite repression of zwf-lacZ with succinate (Fig.…”
Section: Resultssupporting
confidence: 91%
“…When Crc − mutants were grown in the presence of succinate, production of glucose-6-phosphate dehydrogenase, glucokinase, Entner-Doudoroff dehydratase, aldolase, amidase, and the enzymes involved in glucose and mannitol transport were not repressed . The deduced amino acid sequence of the Crc protein showed that it was similar to a family of DNA repair enzymes composed of apurinic\apyrimidinic endonucleases (MacGregor et al, 1996). However, MacGregor et al (1996) were not able to demonstrate in vitro nuclease or DNA-binding activity with purified Crc protein.…”
Section: Introductionmentioning
confidence: 98%
“…The deduced amino acid sequence of the Crc protein showed that it was similar to a family of DNA repair enzymes composed of apurinic\apyrimidinic endonucleases (MacGregor et al, 1996). However, MacGregor et al (1996) were not able to demonstrate in vitro nuclease or DNA-binding activity with purified Crc protein. Thus, the mechanism by which Crc controls catabolite repression in P. aeruginosa is still unclear.…”
Section: Introductionmentioning
confidence: 98%
“…In addition to the above-mentioned pathways for aromatic compounds, it regulates the expression of genes involved in the assimilation of sugars, nitrogenated compounds, and several hydrocarbons (2,8,14,15,22,45,47). Crc represses gene expression posttranscriptionally (15,27,32,47).…”
mentioning
confidence: 99%